Dinámica de reacciones unimoleculares en fase gas: Desviaciones del comportamiento estadístico Dynamics of unimolecular reactions in gas phase: deviations from statistical behavior - Emilio Martínez-Núñez (Química Nova, 2002)
The present review summarizes the most relevant results of our research group obtained recently in the field of unimolecular reaction dynamics. The following processes are specifically analyzed: the isomerization, dissociation and elimination in methyl nitrite, the fragmentation reactions of the mercaptomethyl cation, the C-CO dissociation in the acetyl and propionyl radicals, and the decomposition of vinyl fluoride. In all the cases, only state- or energy-selected systems are considered. Special emphasis is paid to the possibility of systems exhibiting non-statistical behavior.